Mining review data to recommend doctors - Huang, Lingyun (2017)
There are a lot of online reviews on the medical treatments provided by the gynecologists. It will be too laborious for the human beings to process all the reviews at one go. Hence, this final year project is developed to analyze the comments in the web forums and find out the patients’ impressions on their gynecologists. Various measures have been explored to write an entity recognition algorithm in identifying the gynecologists being mentioned in the reviews. Data mining techniques have also been employed to dig out the essential information. Lastly, a web application is developed to let its users to know the relative cost of treatments and the experiences of the treatments with each gynecologist. Statistics on the Top 10 gynecologists in terms of medical experience and cost of treatment are also rendered on the web page.